Below the accountability radar screen:What does state policy say about school counseling? - Eilers, Angela M. (Education Policy Analysis Archives, 2004)
I examine the state policy context of implementing an initiative that transforms the training and role of today’s school counselors. This is essentially a story of political process. Like the implementation of many initiatives, the Transforming School Counselor Initiative (TSCI) is a process of gaining support and then institutionalizing a newly formed vision for the role and function of a profession that has been a part of the school organization for the better part of a century. I examine the educational reform contexts of California, Florida, Georgia, Indiana and Ohio as it relates to implementing the Initiative. As such, the framework for analysis on state policy context draws from macropolitical processes as a way of examining practices andactions of key state stakeholders, such as the state departments of education, the counseling profession’s state-level association and state legislation and statutory language. The final analysis ranks the 5 states with regard to their institutional capacity to fully implement and stabilize reform initiatives related to school counseling.